2018
DOI: 10.1186/s13024-017-0233-5
|View full text |Cite
|
Sign up to set email alerts
|

α-Synuclein accumulation and GBA deficiency due to L444P GBA mutation contributes to MPTP-induced parkinsonism

Abstract: BackgroundMutations in glucocerebrosidase (GBA) cause Gaucher disease (GD) and increase the risk of developing Parkinson’s disease (PD) and Dementia with Lewy Bodies (DLB). Since both genetic and environmental factors contribute to the pathogenesis of sporadic PD, we investigated the susceptibility of nigrostriatal dopamine (DA) neurons in L444P GBA heterozygous knock-in (GBA+/L444P) mice to 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP), a selective dopaminergic mitochondrial neurotoxin.MethodWe used GBA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
138
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(147 citation statements)
references
References 54 publications
8
138
0
1
Order By: Relevance
“…These differences, together with the difference in oxidative stress, that was increased only in gba1 −/− neurons, may contribute to the difference of disease phenotype in the gba1 −/− and gba1 +/− mice. In agreement with our data, a mouse model carrying the heterozygous GBA1 PDassociated mutation L444P was shown to have defective mitochondria, supporting a role of impaired bioenergetics in GBA1-associated PD [57]. Dopaminergic neurons at risk of neurodegeneration in PD are physiologically characterized by Ca 2+ -dependent pace-making activity, while intrinsic Ca 2+ buffering capacity is reduced [22], imposing a major energy demand, which will be amplified by mechanisms that compromise bioenergetic reserve, putting these cells especially at risk [58].…”
Section: Discussionsupporting
confidence: 91%
“…These differences, together with the difference in oxidative stress, that was increased only in gba1 −/− neurons, may contribute to the difference of disease phenotype in the gba1 −/− and gba1 +/− mice. In agreement with our data, a mouse model carrying the heterozygous GBA1 PDassociated mutation L444P was shown to have defective mitochondria, supporting a role of impaired bioenergetics in GBA1-associated PD [57]. Dopaminergic neurons at risk of neurodegeneration in PD are physiologically characterized by Ca 2+ -dependent pace-making activity, while intrinsic Ca 2+ buffering capacity is reduced [22], imposing a major energy demand, which will be amplified by mechanisms that compromise bioenergetic reserve, putting these cells especially at risk [58].…”
Section: Discussionsupporting
confidence: 91%
“…The TPD binding of MTs stabilizes the longitudinal contacts between tubulin subunits and prevents MT disassembly [ 311 ]. In 2018, Zhang and colleagues tested CNDR-51657, a prototype of TPD, on a PS19 transgenic mouse model of tauopathies which expresses the P301S mutant form of human tau and shows the progressive accumulation of neurofibrillary tangles with age [ 294 ]. This study has demonstrated that low doses of CNDR-51657 significantly improved MT density in hippocampal neurons and reduced axonal dystrophy with a resulting reduction in tau pathology.…”
Section: Microtubule-targeting Agentsmentioning
confidence: 99%
“…This study has demonstrated that low doses of CNDR-51657 significantly improved MT density in hippocampal neurons and reduced axonal dystrophy with a resulting reduction in tau pathology. Importantly, no adverse effects were observed in compound-treated mice, including no change in white blood cell counts [ 294 ].…”
Section: Microtubule-targeting Agentsmentioning
confidence: 99%
“…GCase is not directly involved in α‐syn degradation, but its reduced activity/availability promotes the accumulation and aggregation of α‐syn in different cellular cultures and animal models . Mazzulli and colleagues demonstrated, in human cortical neurons, that GCase depletion compromises protein degradation capacity, leading to increased α‐syn levels.…”
Section: The Issue Of Alp Alterations In Sporadic Pdmentioning
confidence: 99%
“…85 GCase is not directly involved in α-syn degradation, but its reduced activity/availability promotes the accumulation and aggregation of α-syn in different cellular cultures and animal models. 63,[86][87][88][89] Mazzulli and colleagues 63 demonstrated, in human cortical neurons, that GCase depletion compromises protein degradation capacity, leading to increased α-syn levels. Furthermore, GCase knockdown and concomitant expression of WT α-syn and A53T α-syn enhanced α-syn-mediated neurotoxicity through formation of soluble and insoluble hMW species.…”
Section: Dysfunction Of the Alp Pathway Leads To Aggregation And Propmentioning
confidence: 99%